Assessing the Link between Language and Identity: The Construction of Identities among Belgian-Turkish Migrants - Zeynep Yılmaz Hava (İnsan & Toplum)
Multiculturalism and multilingualism are inevitable consequences of international migration. Contact between different linguistic or ethnic groups causes the development of expressions specific to one’s identity and for migrants it results in the construction of hybrid identities which are very complex to define and understand without knowing the conditions of their construction processes. This paper aims to contribute to the literature about the identity construction of migrants, to assess the link between language and identity in this process. In this regard, I have pursued a qualitative research focusing on the second-generation Turkish-speaking community in Belgium. As a result of the study, it is observed that the migrants’ ideologies show traces of national discourses most of the time but their actual language performances and practices contradict these ideologies. The immigrants facing institutional or cultural racism in the host country create new multidimensional and transnational spheres in which they perform multiple identities through varying language usages. This research aims to provide a more comprehensive and deeper analysis regarding the link among language ideologies, linguistic differences and identity construction processes in the contemporary Europe, starting from the Belgian case by taking into account the linguistic aspect in a supra-national environment.